Exploration of flow reaction conditions using machine-learning for enantioselective organocatalyzed Rauhut–Currier and [3+2] annulation sequence. Issue 8 (6th January 2020) - Kondo, Masaru; Wathsala, H. D. P.; Sako, Makoto; Hanatani, Yutaro; Ishikawa, Kazunori; Hara, Satoshi; Takaai, Takayuki; Washio, Takashi; Takizawa, Shinobu; Sasai, Hiroaki
Abstract : A highly atom-economical enantioselective Rauhut–Currier and [3+2] annulation has been established by flow system and machine-learning-assisted exploration of suitable conditions. Abstract : A highly atom-economical enantioselective organocatalyzed Rauhut–Currier and [3+2] annulation sequence has been established by using a flow system. Suitable flow conditions were explored through reaction screening of multiple parameters using machine learning. Eventually, functionalized chiral spirooxindole analogues were obtained in high yield with good ee as a single diastereomer within one minute.